English articles and determiners up close - Lester, Mark, (Practice makes perfect (McGraw-Hill Companies), 2013)
As a non-native speaker of English, you may have trouble with determiners because, unlike true adjectives, the choice of which article, demonstrative, or quantifier to use is dependent on both the meaning and the grammatical form of the particular noun they modify. English Articles and Determiners Up Close helps you untangle this grammar puzzle with clear explanations of how they should be treated and used. And of course you will get hundreds of exercise opportunities to practice, practice, practice your new skills.